(untitled) - Main, M. (Hà Nội, 2000)
Nội dung giới thiệu các cấu trúc dữ liệu cùng các đối tượng khác khi sử dụng ngôn ngữ lập trình C++
Keywords: C+ ( computer program language ),Data strustures ( computer science )